2020
DOI: 10.3390/opt1030020
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Visible Light Communication Channel Modeling under Smoke Conditions and Analogy with Fog Conditions

Abstract: Visible Light Communication (VLC) has gained popularity in research and business in the last decade. This technology aims to combine lighting and communication into a single device. For now, this technology has been thoroughly studied for an indoor environment, but it is sufficiently mature nowadays to consider its outdoor-environment potentials. The key outdoor challenges are the weather variabilities and smoke particles in cities due to pollution or fires. The aim of this is the study and quantification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…where 𝑉 is the visibility range, 𝜆 is the operating wavelength, and 𝑇 is the coefficient that describes the fog thickness. This coefficient can be calculated according to the Kruse model in terms of the visibility factor as [25] 𝑇 = { 1.6, 𝑉 > 50 1.3, 6 < 𝑉 < 50 0.585𝑉 1 3 ⁄ , 𝑉 < 6 .…”
Section: Impact Of Link Distance Under Different Weathermentioning
confidence: 99%
“…where 𝑉 is the visibility range, 𝜆 is the operating wavelength, and 𝑇 is the coefficient that describes the fog thickness. This coefficient can be calculated according to the Kruse model in terms of the visibility factor as [25] 𝑇 = { 1.6, 𝑉 > 50 1.3, 6 < 𝑉 < 50 0.585𝑉 1 3 ⁄ , 𝑉 < 6 .…”
Section: Impact Of Link Distance Under Different Weathermentioning
confidence: 99%
“…On the other hand, other analytical studies showed that under conditions of dry ice, which has proven to have a more significant effect than fog on vehicle connection (with dense fog representing the most challenging environment), it was possible to obtain reliable communication according to the experimental measurements, reaching about 20 m. This was accomplished using image sensors at the receiver side, while the connection using PDs was about 15 m, which was the maximum distance achieved using other modulation schemes [ 103 , 104 , 105 ]. The effects of weather and smoke particles on visible short-range communications were examined and evaluated in [ 106 ]. Other factors with a negatively impact are fires, pollution, and smoke particles, which are also considered significant issues.…”
Section: Technical Challenges In Vehicular Vlc and Solutionsmentioning
confidence: 99%
“…Moreover, the idea of visibility as a starting point for smoke and fog models uses the same kinds of equations to explain the optical attenuation, they induce to adjust the smoke and fog effect ratio. The channel attenuation coefficients were calculated using an energy simulator on the receiving side, considering the actual radiation pattern used in the LED, which reached about one kilometer [ 106 , 107 ].…”
Section: Technical Challenges In Vehicular Vlc and Solutionsmentioning
confidence: 99%
“…Outdoor scenarios, where the weather and other atmospheric phenomena play an important role in the propagation of optical signals [ 32 ], have been experimentally investigated in the OWC field and recently in VLC, as summarized in [ 33 ]. In [ 34 ], an outdoor link of approximately 400 m was experimentally validated, which exploited defocusing the camera, allowing the surface of the LED to be extended and the transfer rate to be increased to 450 bps (bits per second).…”
Section: Related Workmentioning
confidence: 99%